The practice of breast self-examination (BSE) among women living in an urban setting in Malaysia - Minhat, Halimatus Sakdiah; Mustafa, Jamsiah; Mohd Zain, N. (ExcelingTech Publishers, 2014)
Breast cancer is a leading killer among women globally. This study aimed to study the BSE practice and its associated factors among women in Malaysia. A cross sectional study was conducted using a purposive sampling, involving 327 women aged between 20 to 70 years old, attending the Outpatient Department at Kuala Lumpur General Hospital from June 2007 until November 2008. A guided questionnaire was used to explore the personal background of the respondents, practice of BSE, source of health information, history of close contact with breast cancer or benign breast lump patients among other family members or friends, history of attending any health campaign or received any health education programme and their confidence level to perform the BSE on themself. The results showed, only 24.2% from the total respondents were practicing BSE on a monthly basis. Information on BSE was mainly obtained from health pamphlets, magazines or newspapers and television. Factors significantly influenced the practice of BSE were marital status (p=0.016), self-confidence (p=0.004), had attended health campaign (p=0.004), had received health education (p<0.01), received information from doctors (p<0.01) and nurses (p=0.001). However, none of these factors significantly predict the practice of BSE among women in the final predictive model. In conclusion, despite the widespread promotion on the importance of BSE, the level of BSE practice among women living in the urban setting in Malaysia was still considerably low. More effective strategies should be conducted by health authorities and related agencies in order to improve the awareness and practice of BSE among Malaysian women if it is proven that the practice of BSE is effective for early detection of breast cancer.